High-thermal-conductivity PVC floor material and preparation method thereof

By rationally proportioning thermally conductive graphite and other additives in PVC floor materials, the problem of the lack of high thermal conductivity of existing PVC floor materials is solved, and multiple optimization effects such as high thermal conductivity, stability and impact resistance of the material are achieved.

CN119350780APending Publication Date: 2025-01-24SHANDONG LUTHAI HLDG GRP CO LTD GRAPHENE POLYMER COMPOSITES R&D CENT +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411716785.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing PVC flooring materials lack high thermal conductivity and cannot meet the growing user needs.

Method used

By properly proportioning polyvinyl chloride (PVC) and thermally conductive graphite, combined with other additives such as calcium carbonate, plasticizers, stabilizers, lubricants, and impact modifiers, high thermal conductivity PVC floor materials are prepared.

Benefits of technology

It improves the thermal conductivity and molding processability of the material, enhances stability, impact resistance and service life, and is suitable for large-scale industrial production and application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005157054410000091
    Figure BDA0005157054410000091
Patent Text Reader

Abstract

The invention provides a high-thermal-conductivity PVC floor material. The high-thermal-conductivity PVC floor material is prepared from the following raw materials in parts by weight: 80-100 parts of polyvinyl chloride, 30-40 parts of calcium carbonate, 35-40 parts of a plasticizer, 4-5 parts of a stabilizer, 1.5-2 parts of a lubricant, 3-4 parts of an impact modifier and 18-20 parts of heat-conducting graphite. The invention also provides a preparation method of the high-thermal-conductivity PVC floor material. The invention has the following advantages: the PVC and the heat-conducting graphite are reasonably proportioned, so the compatibility of the PVC and the heat-conducting graphite can be improved, and the material not only has excellent molding processability of plastic, but also has lower density and more excellent heat-conducting characteristic; a floor made of the high-thermal-conductivity PVC floor material has the advantages of high stability, difficulty in corrosion, excellent thermal conductivity and thermal insulation performance, good impact resistance, long service life and the like, and can be industrially produced and applied on a large scale.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of PVC materials, and in particular to a high thermal conductivity PVC floor material and a preparation method thereof. Background Art

[0002] Flooring, that is, the surface layer of the ground or floor of a house, is a kind of building material. At present, the commonly used composite flooring is solid wood composite flooring or marble tile flooring. Among them, although solid wood composite flooring has many advantages such as beauty and durability, the wood material is easily affected by moisture, has poor thermal insulation performance and high maintenance cost. Although marble tile flooring is strong in material and has strong thermal insulation performance, it has color difference, insufficient elasticity, easy to break, easy to be polluted, and has high requirements for the use environment. Nowadays, polyvinyl chloride composite materials are increasingly used in the building materials market.

[0003] Polyvinyl chloride, referred to as PVC, is a polymer material obtained by polymerization of vinyl chloride monomer. PVC is the world's largest general-purpose plastic with a wide range of applications. At present, most PVC floor materials on the market are mainly characterized by antibacterial, wear-resistant and anti-slip properties, such as the existing technology: CN116922904B. There are relatively few developments on thermal conductive floors.

[0004] Nowadays, with the rapid economic development, the construction industry has also undergone tremendous changes. More and more PVC composite materials are recognized in the building materials market, but if they only have ordinary characteristics, they will be increasingly unable to meet the growing needs of users. In this regard, it is urgent to update the technology of PVC floor materials to make them have the characteristics of high thermal conductivity. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a high thermal conductivity PVC floor material and a preparation method thereof.

[0006] The present invention adopts the following technical solutions to solve the above technical problems:

[0007] A high thermal conductivity PVC floor material comprises the following raw materials in parts by weight: 80-100 parts of polyvinyl chloride (PVC), 30-40 parts of calcium carbonate, 35-40 parts of plasticizer, 4-5 parts of stabilizer, 1.5-2 parts of lubricant, 3-4 parts of impact modifier and 18-20 parts of thermal conductive graphite.

[0008] As one of the preferred embodiments of the present invention, the calcium carbonate is industrial grade heavy calcium powder with a specification of 900 to 1250 meshes.

[0009] As one of the preferred embodiments of the present invention, the plasticizer is dioctyl terephthalate.

[0010] As one of the preferred embodiments of the present invention, the stabilizer is a solid calcium-zinc composite stabilizer.

[0011] As one of the preferred embodiments of the present invention, the lubricant is at least one of calcium stearate, polyethylene wax, and polyol fatty acid ester.

[0012] As one of the preferred embodiments of the present invention, the impact modifier includes chlorinated polyethylene, acrylate copolymer and methyl methacrylate copolymer, and the mixing mass ratio of the three is (2.8-3.2):1:1 respectively.

[0013] As one of the preferred embodiments of the present invention, in the acrylic acid ester copolymer, the mass ratio of acrylic acid to acrylic acid ester is 1:(1.8-2.2).

[0014] As one of the preferred embodiments of the present invention, in the methyl methacrylate copolymer, the mass ratios of methyl methacrylate, butadiene and styrene are 7:2:1 respectively.

[0015] As one of the preferred embodiments of the present invention, the thermally conductive graphite is graphene nanosheets with a carbon content of 95% to 99.9% and a particle size of 50 μm.

[0016] A method for preparing the above-mentioned high thermal conductivity PVC floor material comprises the following steps:

[0017] S1. Blending polyvinyl chloride and thermal conductive graphite first, and then adding the remaining raw materials to continue mixing in a high-speed mixer; during mixing, heating the materials to a first temperature, discharging the materials, and cooling them to a second temperature;

[0018] S2, feeding the material obtained in step S1 into a screw extruder, and extruding and cooling after melt mixing;

[0019] S3, placing the material obtained in step S2 into a template machine for compression molding;

[0020] S4. Put the pressed board into a module cutting machine and cut it into blocks to obtain high thermal conductivity PVC floor blocks.

[0021] As one of the preferred embodiments of the present invention, in step S1, when polyvinyl chloride and thermal conductive graphite are blended, the speed of the high-speed mixer is 1000-1500 r / min, and the mixing and stirring time is 8-10 min; when the remaining raw materials are mixed, the speed of the high-speed mixer is 2500-3000 r / min, and the mixing and stirring time is 30-40 min; and during mixing, the first temperature is 110°C-130°C, and the second temperature is ≤50°C.

[0022] As one of the preferred embodiments of the present invention, in step S2, the barrel of the screw extruder is divided into six zones, I to VI, and the temperatures of each zone are 178-180°C, 180-185°C, 185-190°C, 160-165°C, 165-175°C, and 161-170°C, respectively, and the die head temperature is 165°C; cooling adopts at least one of water cooling and normal temperature cooling; the initial water temperature of water cooling is 35-45°C.

[0023] The advantages of the present invention compared to the prior art are:

[0024] (1) The present invention utilizes a reasonable ratio of PVC and thermally conductive graphite to improve the compatibility of the two, so that the material not only has the excellent molding processability of plastics, but also has a lower density and better thermal conductivity;

[0025] (2) The floor made of the high thermal conductivity PVC floor material of the present invention also has the advantages of high stability, not easy to be corroded, excellent thermal conductivity and heat preservation performance, good impact resistance, and long service life, and can be applied in large-scale industrial production. DETAILED DESCRIPTION

[0026] The embodiments of the present invention are described in detail below. The present embodiments are implemented under the premise of the technical solution of the present invention, and detailed implementation methods and specific operation processes are given, but the protection scope of the present invention is not limited to the following embodiments. Meanwhile, the raw materials used in the following embodiments are conventional raw materials and reagents in this field unless otherwise specified. The experimental conditions and experimental methods used are conventional conditions and methods in this field unless otherwise specified, and will not be repeated.

[0027] Example 1

[0028] A high thermal conductivity PVC floor material of this embodiment is prepared as follows:

[0029] (1) Weigh the raw materials according to the following weight proportions: 80 parts of PVC, 30 parts of industrial-grade calcium carbonate powder with a mesh size of 900, 35 parts of dioctyl terephthalate, 4 parts of solid calcium-zinc composite stabilizer, 1.5 parts of calcium stearate, 3 parts of impact modifier, and 18 parts of graphene nanosheets (carbon content 95%, particle size 50 μm). The impact modifier is composed of a mixture of chlorinated polyethylene, acrylate copolymer and methyl methacrylate copolymer, and the mixing mass ratio is 2.8:1:1; and in the acrylate copolymer, the mass ratio of acrylic acid to acrylate is 1:1.8; in the methyl methacrylate copolymer, the mass ratio of methyl methacrylate, butadiene and styrene is 7:2:1.

[0030] (2) The above-mentioned PVC raw materials and graphene nanosheets in the above-mentioned weight proportions are first blended, and during blending, the speed of the high-speed mixer is 1000 r / min, and the mixing time is 8 min; then, the remaining other raw materials are added and continued to be mixed in the high-speed mixer, and the speed of the high-speed mixer is 2500 r / min, and the mixing time is 30 min; and during mixing, the materials are heated to 110° C., discharged, and cooled to 30° C.

[0031] (3) feeding the material obtained in step (2) into a screw extruder, extruding after melt mixing, and cooling by water; wherein the barrel of the screw extruder is divided into six zones, I to VI, and the temperatures of the zones are 178° C., 180° C., 185° C., 160° C., 165° C., and 161° C., respectively, and the die head temperature is 165° C.; and the initial water temperature of the water cooling is 35° C.

[0032] (4) The material obtained in step (3) is placed in a template machine for compression molding.

[0033] (5) The pressed sheet is placed into a module cutting machine and cut into blocks.

[0034] Example 2

[0035] A high thermal conductivity PVC floor material of this embodiment is prepared as follows:

[0036] (1) Weigh the raw materials according to the following weight proportions: 90 parts of PVC, 35 parts of industrial-grade calcium carbonate powder with a mesh size of 1000, 36 parts of dioctyl terephthalate, 4.5 parts of solid calcium-zinc composite stabilizer, 1.8 parts of polyethylene wax, 3.5 parts of impact modifier, and 19 parts of graphene nanosheets (carbon content 98%, particle size 50 μm). The impact modifier is composed of a mixture of chlorinated polyethylene, acrylate copolymer and methyl methacrylate copolymer, and the mixing mass ratio is 3:1:1; and in the acrylate copolymer, the mass ratio of acrylic acid to acrylate is 1:2; in the methyl methacrylate copolymer, the mass ratio of methyl methacrylate, butadiene and styrene is 7:2:1.

[0037] (2) The above-mentioned PVC raw materials and graphene nanosheets are first blended at a high-speed mixer speed of 1200 r / min and a mixing time of 9 min. Then, the remaining other raw materials are added and continued to be mixed in the high-speed mixer at a high-speed mixer speed of 2800 r / min and a mixing time of 35 min. During mixing, the materials are heated to 120° C., discharged, and cooled to 40° C.

[0038] (3) feeding the material obtained in step (2) into a screw extruder, extruding after melt mixing, and cooling at room temperature; wherein the barrel of the screw extruder is divided into six zones, I to VI, and the temperatures of the zones are 179° C., 181° C., 186° C., 163° C., 168° C., and 165° C., respectively, and the die head temperature is 165° C.

[0039] (4) The material obtained in step (3) is placed in a template machine for compression molding.

[0040] (5) The pressed sheet is placed into a module cutting machine and cut into blocks.

[0041] Example 3

[0042] A high thermal conductivity PVC floor material of this embodiment is prepared as follows:

[0043] (1) Weigh the raw materials according to the following weight proportions: 100 parts of PVC, 40 parts of industrial-grade calcium carbonate powder with a mesh size of 1250, 40 parts of dioctyl terephthalate, 4 parts of solid calcium-zinc composite stabilizer, 2 parts of calcium stearate, 4 parts of impact modifier, and 20 parts of graphene nanosheets (carbon content 99.9%, particle size 50 μm). The impact modifier is composed of a mixture of chlorinated polyethylene, acrylate copolymer and methyl methacrylate copolymer, and the mixing mass ratio is 3:1:1; and in the acrylate copolymer, the mass ratio of acrylic acid to acrylate is 1:2; in the methyl methacrylate copolymer, the mass ratio of methyl methacrylate, butadiene and styrene is 7:2:1.

[0044] (2) The above-mentioned PVC raw materials and graphene nanosheets in the above-mentioned weight proportions are first blended, and during blending, the speed of the high-speed mixer is 1200 r / min, and the mixing time is 9 min; then, the remaining other raw materials are added and continued to be mixed in the high-speed mixer, and the speed of the high-speed mixer is 2800 r / min, and the mixing time is 36 min; and during mixing, the materials are heated to 125° C., discharged, and cooled to 30° C.

[0045] (3) feeding the material obtained in step (2) into a screw extruder, extruding after melt mixing, and cooling by water; wherein the barrel of the screw extruder is divided into six zones, I to VI, and the temperatures of the zones are 178° C., 181° C., 186° C., 163° C., 168° C., and 165° C., respectively, and the die head temperature is 165° C.; and the initial water temperature of the water cooling is 40° C.

[0046] (4) The material obtained in step (3) is placed in a template machine for compression molding.

[0047] (5) The pressed sheet is placed into a module cutting machine and cut into blocks.

[0048] Example 4

[0049] A high thermal conductivity PVC floor material of this embodiment is prepared as follows:

[0050] (1) Weigh the raw materials according to the following weight proportions: 100 parts of PVC, 40 parts of industrial-grade calcium carbonate powder with a mesh size of 1250, 40 parts of dioctyl terephthalate, 5 parts of solid calcium-zinc composite stabilizer, 2 parts of polyol fatty acid ester, 4 parts of impact modifier, and 20 parts of graphene nanosheets (carbon content 99.9%, particle size 50 μm). The impact modifier is composed of a mixture of chlorinated polyethylene, acrylate copolymer and methyl methacrylate copolymer, and the mixing mass ratio is 3.2:1:1; and in the acrylate copolymer, the mass ratio of acrylic acid to acrylate is 1:2.2; in the methyl methacrylate copolymer, the mass ratio of methyl methacrylate, butadiene and styrene is 7:2:1.

[0051] (2) The above-mentioned PVC raw materials and graphene nanosheets are first blended at a high-speed mixer speed of 1500 r / min for 10 min; then, the remaining other raw materials are added and continued to be mixed in the high-speed mixer at a high-speed mixer speed of 3000 r / min for 40 min; and during mixing, the materials are heated to 130° C., discharged, and cooled to 50° C.

[0052] (3) feeding the material obtained in step (2) into a screw extruder, extruding after melt mixing, and cooling by water; wherein the barrel of the screw extruder is divided into six zones, I to VI, and the temperatures of the zones are 180° C., 185° C., 190° C., 165° C., 175° C., and 170° C., respectively, and the die head temperature is 165° C.; and the initial water temperature of the water cooling is 45° C.

[0053] (4) The material obtained in step (3) is placed in a template machine for compression molding.

[0054] (5) The pressed sheet is placed into a module cutting machine and cut into blocks.

[0055] Comparative Example 1

[0056] The preparation method of a PVC floor material in this comparative example is basically the same as that of Example 3, with the main difference being that no graphene nanosheets are added.

[0057] Comparative Example 2

[0058] The preparation method of a PVC floor material in this comparative example is basically the same as that of Example 3, with the main difference being that ordinary graphite (with a carbon content of 99% and a particle size of 50 μm) is used instead of the graphene nanosheets in Example 3.

[0059] Comparative Example 3

[0060] The preparation method of a PVC floor material in this comparative example is basically the same as that of Example 3, except that chlorinated polyethylene, acrylate copolymer and methyl methacrylate copolymer (impact modifier) ​​are not added.

[0061] Comparative Example 4

[0062] The preparation method of a PVC floor material in this comparative example is basically the same as that of Example 3, with the main difference being that no chlorinated polyethylene (impact modifier) ​​is added.

[0063] Comparative Example 5

[0064] The preparation method of a PVC floor material in this comparative example is basically the same as that of Example 3, with the main difference being that no acrylic ester copolymer (impact modifier) ​​is added.

[0065] Comparative Example 6

[0066] The preparation method of a PVC floor material in this comparative example is basically the same as that of Example 3, with the main difference being that no methyl methacrylate copolymer (impact modifier) ​​is added.

[0067] Experimental Example 1

[0068] This experimental example is used to verify the effect of "graphene nanosheets" on the thermal conductivity of the PVC floor material of the present invention.

[0069] The thermal conductivity of the floor materials prepared according to the present invention (Example 3) and Comparative Examples 1 and 2 was tested, and the test results are shown in Table 1.

[0070] Table 1 Thermal conductivity data of the present invention and comparative examples 1 and 2

[0071] Test items The present invention Comparative Example 1 Comparative Example 2 Thermal conductivity (W / (m·K)) 0.943 0.325 0.515

[0072] It can be seen from the results in Table 1 that: (1) compared with the comparative example 1 in which no graphite material is added, the thermal conductivity of the PVC floor material prepared by the method of the present invention is improved by about 3 times; (2) compared with the comparative example 2 in which ordinary graphite is added, the thermal conductivity of the PVC floor material prepared by the method of the present invention is improved by about 2 times; indicating that the addition of graphene nanosheets (thermal conductive graphite) plays a key role in improving the thermal conductivity of the material. The present invention utilizes a reasonable ratio of PVC and thermal conductive graphite to improve the compatibility of the two, so that the material not only has excellent molding processability of plastics, but also has better thermal conductivity characteristics.

[0073] Experimental Example 2

[0074] This experimental example is used to verify the effect of the "impact modifier" on the impact resistance of the PVC floor material of the present invention.

[0075] The floor materials prepared according to the present invention (Example 3) and Comparative Examples 3 to 6 were tested for impact resistance. The test results are shown in Table 2.

[0076] Table 2 Bending strength and impact resistance data of the present invention and comparative examples 3, 4, 5, and 6

[0077]

[0078] It can be seen from the results in Table 2 that the combined addition of chlorinated polyethylene, acrylate copolymer and methyl methacrylate copolymer plays an important role in improving the bending strength and impact resistance of the material, and none of the three can be missing.

[0079] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A high thermal conductivity PVC floor material, characterized in that: The invention comprises the following raw materials in parts by weight: 80-100 parts of polyvinyl chloride, 30-40 parts of calcium carbonate, 35-40 parts of plasticizer, 4-5 parts of stabilizer, 1.5-2 parts of lubricant, 3-4 parts of impact modifier and 18-20 parts of thermal conductive graphite.

2. The high thermal conductivity PVC floor material according to claim 1, characterized in that: The calcium carbonate is industrial grade heavy calcium powder with a specification of 900-1250 meshes.

3. The high thermal conductivity PVC floor material according to claim 1, characterized in that: The plasticizer is dioctyl terephthalate.

4. The high thermal conductivity PVC floor material according to claim 1, characterized in that: The stabilizer is a solid calcium-zinc composite stabilizer.

5. The high thermal conductivity PVC floor material according to claim 1, characterized in that: The lubricant is at least one of calcium stearate, polyethylene wax, and polyol fatty acid ester.

6. The high thermal conductivity PVC floor material according to claim 1, characterized in that: The impact modifier comprises chlorinated polyethylene, acrylate copolymer and methyl methacrylate copolymer, and the mixing mass ratio of the three is (2.8-3.2):1:1 respectively.

7. The high thermal conductivity PVC floor material according to claim 1, characterized in that: The thermally conductive graphite is graphene nanosheets with a carbon content of 95% to 99.9% and a particle size of 50 μm.

8. A method for preparing a high thermal conductivity PVC floor material according to any one of claims 1 to 7, characterized in that: The steps include: S1. Blending polyvinyl chloride and thermal conductive graphite first, and then adding the remaining raw materials to continue mixing in a high-speed mixer; during mixing, heating the materials to a first temperature, discharging the materials, and cooling them to a second temperature; S2, feeding the material obtained in step S1 into a screw extruder, and extruding and cooling after melt mixing; S3, placing the material obtained in step S2 into a template machine for compression molding; S4. Put the pressed board into a module cutting machine and cut it into blocks to obtain high thermal conductivity PVC floor blocks.

9. The method for preparing a high thermal conductivity PVC floor material according to claim 8, characterized in that: In the step S1, when polyvinyl chloride and thermal conductive graphite are blended, the speed of the high-speed mixer is 1000-1500 r / min, and the mixing time is 8-10 min; when the remaining raw materials are mixed, the speed of the high-speed mixer is 2500-3000 r / min, and the mixing time is 30-40 min; and during mixing, the first temperature is 110° C.-130° C., and the second temperature is ≤50° C.

10. The method for preparing a high thermal conductivity PVC floor material according to claim 8, characterized in that: In the step S2, the barrel of the screw extruder is divided into six zones, and the temperatures of each zone are 178-180°C, 180-185°C, 185-190°C, 160-165°C, 165-175°C, and 161-170°C, respectively, and the die head temperature is 165°C; cooling adopts at least one of water cooling and normal temperature cooling; the initial water temperature of water cooling is 35-45°C.

Citation Information

Patent Citations

  • A PVC floor with anti-slip properties and its preparation method

    CN116922904B